Enhancing Phenol Conversion Rates in Saline Anaerobic Membrane Bioreactor Using Acetate and Butyrate as Additional Carbon and Energy Sources - García Rea, Víctor S.; Muñoz Sierra, Julian D.; Fonseca Aponte, Laura M.; Cerqueda-Garcia, Daniel; Quchani, Kiyan M.; Spanjers, Henri; van Lier, Jules B. (Frontiers in Microbiology, 2020)
Phenolic industrial wastewater, such as those from coal gasification, are considered a challenge for conventional anaerobic wastewater treatment systems because of its extreme characteristics such as presence of recalcitrant compounds, high toxicity, and salinity. However, anaerobic membrane bioreactors (AnMBRs) are considered of potential interest since they retain all micro-organism that are required for conversion of the complex organics. In this study, the degradation of phenol as main carbon and energy source (CES) in AnMBRs at high salinity (8.0 g Na+·L-1) was evaluated, as well as the effect of acetate and an acetate-butyrate mixture as additional CES on the specific phenol conversion rate and microbial community structure. Three different experiments in two lab-scale (6.5 L) AnMBRs (35 °C) were conducted. The first reactor (R1) was fed with phenol as the unique CES, the second reactor was fed with phenol and either acetate [2 gCOD·L-1], or a 2:1 acetate-butyrate [2 gCOD·L 1] mixture as additional CES. Results showed that phenol conversion could not be sustained when phenol was the sole CES. In contrast, when the reactor was fed with acetate or acetate-butyrate mixture, specific phenol conversion rates of 115 and 210 mgPh·gVSS-1d-1, were found respectively. The syntrophic phenol degrader Syntrophorhabdus sp. and the acetoclastic methanogen Methanosaeta sp. were the dominant bacteria and archaea, respectively, with corresponding relative abundances of up to 63% and 26%. The findings showed that dosage of additional CES allowed the development of a highly active phenol degrading biomass, potentially improving the treatment of industrial and chemical wastewaters.